Improving the Skill of the Women Farmer Group "Widya Pertiwi" in Belantih Village, Bangli, to Enhance the Value-Added of Citrus Fruit Processing in Production Outcomes.: Efforts to Process Citrus Fruits to Increase the Added Value of Production Results - Ni Komang Alit, Astiari; Ni Putu, Anom Sulistiawati; Suaria, I Nengah; Ayu Suardani Singapurwa, Ni Made; Sutapa, I Gede; Putri Risa Andriani, Anak Agung Sagung P; Chinta Dewi, I Gusti Ayu (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Belantih Village, located in the Kintamani District of the Bangli Regency, is recognized for its substantial citrus fruit potential. The majority of the local population in this region engage in citrus farming as their primary means of income. The lack of knowledge among citrus growers in Belantih Village about the processing of citrus fruits into long-lasting processed products is evident. The primary objective of the community service activities is to enhance knowledge and expertise in the processing of citrus fruits into value-added products, hence extending their shelf life and augmenting their economic worth. The implementation of counseling and mentorship programs, technological transfer initiatives, and training sessions focused on the processing of oranges into jam. The individuals included in this study were members of the women farmer group known as "Widya Pertiwi". The service activity consists of several steps, including the provision of materials and demonstrations on citrus processing, followed by a final evaluation in the form of a post-test administered through the distribution of questionnaires. The outcomes of counseling and training revealed that participants, utilizing the experiential learning approach and training, expressed their ability to comprehend and effectively execute the processing of citrus fruits into various culinary derivatives. This skill acquisition was particularly beneficial during periods of abundant fruit harvest, as it allowed for the generation of increased value and income. The findings of the study indicated a significant improvement in general knowledge. Specifically, 93.33% of participants reported a clear understanding, while the remaining 6.67% expressed comprehension regarding the processing of citrus fruits into value-added products following the completion of the service activities. Notably, no respondents reported a lack of understanding or confusion. The findings indicate that all participants belonging to the Women Farmers group have a keen interest in enhancing their competencies and implementing citrus fruit processing techniques to produce jam products. This approach aims to mitigate fruit rotting during periods of ample fruit availability.